The mechanism for ensuring human rights under contemporary state - Lysak, Maksym; Лисак, Максим Юрійович (: ТОВ "Наукова установа "Правові горизонти", 2025)
This article is devoted to a comprehensive analysis of the mechanism for ensuring human rights in the context of contemporary state-building processes. The main theoretical and legal approaches to understanding the content and purpose of this mechanism are examined, and the key challenges faced by the state in the course of establishing democratic principles and developing effective legal institutions are identified. It is substantiated that the mechanism for ensuring human and civil rights and freedoms constitutes a multicomponent system that integrates legal, organizational, economic, and institutional means aimed at the effective realization, protection, and restoration of violated rights. The article argues that the right to protection is implemented through a system of diverse mechanisms that ensure not only the formal enshrinement of rights but also their practical realization, safeguarding, and defense. Within the structure of this mechanism, a distinction is proposed between a static component, which encompasses normative legal guarantees, the range of subjects involved, and forms of legal liability, and a dynamic component, which reflects the procedural aspect of the realization, safeguarding, and protection of rights through the activities of authorized institutions. Special attention is paid to the impact of transformational processes within the state on the effectiveness of the human rights protection mechanism, and the necessity of its modernization in line with international and European standards is substantiated. The specific features of the realization of rights and freedoms under martial law, demographic changes, economic instability, and global social challenges are analyzed. It is emphasized that the protection of human rights under such conditions requires an integrated approach combining legal, administrative, and socio-economic instruments. The multidimensional nature of the state-building process is highlighted, encompassing legal, political, economic, ideological, security, financial, and cultural-value factors. The research findings have practical significance and may be used to further improve the mechanism for ensuring human rights in the context of contemporary state-building
Keywords: human rights; state-building; mechanism for ensuring rights; rule of law; martial law; civil society